Insight into Drug Production Cost Estimation - Malak Shmela; Hala Almalian; Assad Elmhgoubi; Nagib Elmarzugi (AlQalam Journal of Medical and Applied Sciences, 2025)
The pharmaceutical industry is committed to innovate high-quality products that address medical demands globally. In this industry, the production costs constitute a significant portion of overall expenditures, where in 2016, the sector generated approximately 1 trillion in annual revenue, which increased to around 1.6 trillion by 2023. Product costing involves calculating all expenses associated with product development, covering both direct costs—such as raw materials and labor—and indirect costs, including administrative overhead. As a result, numerous studies have analyzed trends across various expense and income categories, with a particular focus on production costs. These studies seek to analyze the connections and variations in cost across various pharmaceutical companies, such as brand-name, generic, and biotech companies. Manufacturers estimate production expenses using current data to identify and mitigate hidden costs resulting from inefficient practices. This study conducted a detailed analysis of drug production costs, presenting two practical examples: Entecavir® and Orlistat®. The production costs of these drugs were examined based on the methodologies outlined in the study. يُعَدّ قطاع الصناعات الدوائية من المجالات الحيوية التي تسعى إلى تطوير منتجات مبتكرة وعالية الجودة لتلبية الاحتياجات الطبية العالمية. وتشكّل تكاليف الإنتاج نسبة كبيرة من إجمالي النفقات التشغيلية في هذا القطاع. تناول هذه الدراسة تكاليف إنتاج الأدوية في الصناعة الدوائية، حيث يتم حسابها من خلال مرحلتين رئيسيتين: البحث والتطوير والتصنيع الكلي، والذي يشمل المواد المباشرة، العمالة المباشرة والنفقات العامة للتصنيع. كما يتم تحليل تكاليف التعبئة والتغليف، ووضع العلامات، والاختبارات التي تضمن مطابقة الدواء إلى معايير الجودة. يسلط التحليل الضوء على التكاليف المباشرة وغير المباشرة للإنتاج، مع التركيز على تحسين الكفاءة التشغيلية، وكان الهدف من هذه الدراسة تقديم نظرة شاملة حول تقدير تكاليف الإنتاج الدوائي، وتحليل التكاليف عبر المراحل المختلفة، واستكشاف سبل تحسينها من خلال اعتبارات اقتصادية أثناء التصنيع. هذه الدراسة قد قدمت مثالين لتكلفة إنتاج دواء للمريض وهم دواء Entecavir® ودواء Orlistat® وقد قدمت ذلك بالتفصيل وفقا لأليات تكاليف الإنتاج المذكورة سابقا في هذه الدراسة